2023
DOI: 10.1001/jamaoto.2023.2021
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Academic Productivity Trends Among American Head & Neck Society Fellows Over a 20-Year Period

Abstract: ImportanceHistorical data reveal that, compared with women, men are more likely to pursue a head and neck surgical oncology fellowship, but little is known about possible gender differences in academic productivity.ObjectiveTo assess demographic trends and academic productivity among American Head & Neck Society (AHNS) fellowship graduates.Design, Setting, and ParticipantsThis cross-sectional study used electronically published data from the AHNS on fellowship graduates in the US and Canada from Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…24,25 A more recent study of American Head & Neck Society fellowship graduates found that early in career men and women had similar hindex scores and that the difference in h-index widened as surgeons progressed through their careers. 26 The findings of our study align with the initial studies and show that at a career duration of 11-20 years, men have higher h-index and w-RCR than women, with all other bibliometrics being similar across career duration. When stratified by academic rank, among assistant professors, men had higher h-index than women, with similar research productivity across higher academic ranks.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…24,25 A more recent study of American Head & Neck Society fellowship graduates found that early in career men and women had similar hindex scores and that the difference in h-index widened as surgeons progressed through their careers. 26 The findings of our study align with the initial studies and show that at a career duration of 11-20 years, men have higher h-index and w-RCR than women, with all other bibliometrics being similar across career duration. When stratified by academic rank, among assistant professors, men had higher h-index than women, with similar research productivity across higher academic ranks.…”
Section: Discussionsupporting
confidence: 90%
“…1). Men had higher median (IQR) h-index (16 [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] vs 9 [6][7][8][9][10][11][12][13][14]) and w-RCR (51.8 [17.4-101.2] vs. 23.0 [13.0-37.4]) than women (both p < 0.001) (Table IV). Men and women had similar m-RCRs (1.3 [1.0-1.9] vs. 1.3 [1.0-1.8], p = 0.269).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over time, there has been an increase in the representation of females in academic otolaryngology in HICs [19 ▪ ,20,21], although discrepancies continue to be documented in academic medicine.…”
Section: Recent Findingsmentioning
confidence: 99%